Modified Data Envelopment Analysis Model Based on Service Quality Concept for Vendor Selection - Hassan, Nura Ibrahim (Eastern Mediterranean University EMU, 2017)
Purchasing function is the key part of the logistics management in firms, and the prime responsibility for this function is the selection of appropriate vendors i.e. the most efficiently performing vendors. Many analytical and conceptual models for tackling the vendor selection problem have been established. Several criteria are to be considered in evaluating vendors’ relative efficiencies, hence this problem is being recognized as multiple criteria decision making problem. Researchers developed techniques for tackling this multi criteria efficiency evaluation problems in recent years by applying Data Envelopment Analysis (DEA) being the most effective method for evaluating vendor efficiencies, but all their researches did not address the issue of weakly efficient vendors in the DEA. Therefore, this thesis introduce a modified method for figuring vendors efficiency with the issue of weak efficient vendors being properly addressed so that only truly efficient vendors are selected in the appropriation situation. The modified method uses facet analysis in modifying the standard DEA model employed by several researchers in evaluating the vendors’ efficiencies. The criteria chosen in these models are service quality, rate of rejected items, late deliveries and price. The results and comparisons between the modified and standard DEA model shows that the modified DEA model gives a better and true efficiency scores of vendors, this greatly improve the vendor evaluation and selection methods. Keywords: Modified Data Envelopment Analysis, Vendor Evaluation and Selection, Service Quality

ÖZ: Şirketlerde lojistik yönetiminin temel kısmı satın alma fonksiyonudur ve bu fonksiyonun başlıca sorumluluğu, uygun satıcıları, yani en verimli şekilde çalışan satıcıları seçmektir. Satıcı seçimi problemini çözmek için birçok analitik ve kavramsal model geliştirilmiştir. Satıcıların göreli verimliliklerinin değerlendirilmesinde çeşitli kriterler göz önüne alınmalıdır, bu nedenle satıcı seçim problemi çok kriterli karar verme problemi olarak kabul edilmektedir. Son yıllarda, araştırmacılar, bu çok ölçütlü verimlilik değerlendirme sorunlarını, Veri Zarflama Analizi'ni (VZA) en etkin değerlendirme yöntemi olarak uygulayarak, çözmek için teknikler geliştirmişlerdir ancak tüm bu araştırmalar, VZA'daki zayıf verimli satıcıların sorununu ele almamaktadır. Bu nedenle, bu tez, zayıf verimli satıcıların uygun bir şekilde ele alınması sorunu ile satıcıları değerlendirmek için modifiye edilmiş bir yaklaşım sunmakta ve böylece yalnızca bir tedarik durumunda gerçekten verimli satıcılar seçilmektedir. Değiştirilen yaklaşım, satıcıların verimliliklerini değerlendirirken birçok araştırmacı tarafından kullanılan standart VZA modelinin modifikasyonunda faset analizini kullanmaktadır. Bu modellerde göz önüne alınan kriterler, hizmet kalitesi, fiyat, geç teslimat ve reddedilen parçalardır. Modifiye ve standart VZA modeli arasındaki sonuçlar ve karşılaştırmalar, modifiye VZA modelinin satıcıların daha iyi ve gerçek etkinlik skorları verdiğini, bunun da satıcı değerlendirme ve seçim yöntemlerini büyük ölçüde iyileştirdiğini göstermektedir. Anahtar Kelimeler: Veri Zarflama Analizi, Satıcı Seçimi, Servis Kalitesi
Master of Science in Industrial Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Industrial Engineering, 2017. Supervisor: Assist. Prof. Dr. Sahand Daneshvar.
Keywords: Industrial Engineering; Vendor selection-management; Modified Data Envelopment Analysis; Vendor Evaluation and Selection; Service Quality